2020
DOI: 10.1089/cap.2019.0057
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use, Mental Health, and Child Welfare Profiles of Juvenile Justice-Involved Commercially Sexually Exploited Youth

Abstract: Objectives: To describe the substance use profiles of youth impacted by commercial sexual exploitation (CSE) and explore associations between substance use with mental health diagnoses and child welfare involvement. Methods: Data were systematically extracted from the court files of 364 youth who participated between 2012 and 2016 in Los Angeles County's Succeeding Through Achievement and Resilience (STAR) Court, a juvenile delinquency specialty court for youth impacted by CSE. Descriptive statistics and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Based on the results of this research, it is clear that Los Angeles County’s CWS must be significantly reformed with regard to how it intervenes in cases of IPV. Many advocates and policymakers have recently proposed bringing together multidisciplinary teams to put forward policy changes, make child removal decisions, and evaluate child removal decisions (Bai et al, 2019 ; Bath et al, 2020 ; Herbert & Bromfield, 2019 ; Ogbonnaya & Keeney, 2018 ; Trubek & Farnham, 2000 ). Our study’s findings illuminate how each professional’s professional and legal duties influence their decision-making within the CWS.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of this research, it is clear that Los Angeles County’s CWS must be significantly reformed with regard to how it intervenes in cases of IPV. Many advocates and policymakers have recently proposed bringing together multidisciplinary teams to put forward policy changes, make child removal decisions, and evaluate child removal decisions (Bai et al, 2019 ; Bath et al, 2020 ; Herbert & Bromfield, 2019 ; Ogbonnaya & Keeney, 2018 ; Trubek & Farnham, 2000 ). Our study’s findings illuminate how each professional’s professional and legal duties influence their decision-making within the CWS.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, one of the few CSEC specialty courts that has been examined empirically is the STAR (Succeed through Achievement and Resilience) Court in Los Angeles, CA (Bacharach et al, 2020). Data published on youth who have participated in this specialty court suggest that youth who have experienced exploitation have histories of adversity (e.g., child welfare involvement), educational concerns, and significant mental health and substance use issues (Bacharach et al, 2020; Bath et al, 2020a; Cook et al, 2018). Cook et al (2018) found relationships between substance use and mental health concerns, as well as substance use and histories of abuse, suggesting the need for trauma‐responsive behavioral health interventions.…”
Section: Youth Who Have Experienced Sexual Exploitation and The Juven...mentioning
confidence: 99%
“…Adopting a prevention perspective in this preliminary test of the protective role of informal mentor support, we used a broad index of adolescents' involvement in substance use rather than their use of specific substances. Thus, we asked participants to report their use of various substances but combined those reports to form a dichotomous variable indicating involvement or lack of involvement in substance use (Bath et al, 2020). We tested four hypotheses.…”
Section: The Present Studymentioning
confidence: 99%